A Socioeconomic Analysis of the Effects of International Sanctions on Targeted Nations - Suleiman, Nashwan Mohammed; Ahmed, Sundus Serhan; Zuhair, Mohammed; Dahash, Zahraa Mahdi; Chornomordenko, Ivan (Journal of Ecohumanism, 2024)
Background: International sanctions are increasingly used to impose and achieve policy changes in targeted states. However, these sanctions have had complex effects on targeted nations’ socioeconomic frameworks, prompting academic examination. Objective: This study examines the socioeconomic effects of international sanctions on the nations that impose them, focusing on whether they achieve the desired policy changes or worsen the citizens’ plight. Methods: A meta-analysis of case studies on nations sanctioned during the previous 30 years was done. This allowed the compilation of data on economic indicators, social welfare, and political stability in the context of sanctions. At the same time, a multi-variable regression model isolated the unique consequences of these economic coercive measures. Results: Preliminary findings show that while international sanctions often yield short-term political gains, they also have adverse socioeconomic effects on civilians, including increased poverty, poor health outcomes, and infrastructural decay, often disproportionately affecting the most vulnerable. Conclusion: International sanctions have a complicated relationship between policy goals and the socioeconomic impoverishment of targeted states. This requires rethinking foreign policy and promoting more compassionate and effective methods that protect populations while attaining diplomatic and policy goals.